The privacy awakening: the urgent need to harmonise the right to privacy in Africa (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:This article argues that, although the African Charter on Human and Peoples’ Rights does not expressly provide for a right to privacy, the African Commission on Human and Peoples’ Rights can and should -- of its own volition or when called upon to do so -- read the right to privacy into the African Charter on Human and Peoples’ Rights in order to harmonise the African human rights system and provide express recognition to privacy as a fundamental and enforceable human right in Africa. Drawing on the approach taken by the African Commission in Social and Economic Rights Action Centre and Another v Nigeria and comparative jurisprudence from the Supreme Court of India in Justice KS Puttaswamy (Retd) and Another v Union of India and Others, this article explores how the right to privacy can be read into the African Charter through the right to respect for life and the integrity of the person, the right to dignity, and the right to liberty and security of the person. This article submits that reading the right to privacy into the African Charter is the least imposing and swiftest measure available, and one that mitigates the need to amend the African Charter in terms of its articles 66 or 68. It concludes with arguments as to why it is necessary and important to read the right to privacy into the African Charter, and the broader impact that its enforceability can have on the meaningful realisation of the right to privacy and other associated rights in the region. TITRE ET RÉSUMÉ EN FRANCAIS:L’essor du droit a la vie privée: de l’urgente necessite d’une harmonisation du droit a la vie privée en AfriqueRÉSUMÉ:Cette contribution avance que, bien que la Charte africaine des droits de l’homme et des peuples ne garantit pas expressément le droit à la vie privée, la Commission africaine des droits de l’homme et des peuples peut et doit - de sa propre initiative ou lorsqu’elle est saisie - déduire l’existence du droit à la vie privée des dispositions de la Charte africaine afin d’harmoniser le système africain des droits de l’homme et de reconnaître expressément le droit à la vie privée en tant que droit fondamental et applicable en Afrique. S’appuyant sur l’approche adoptée par la Commission africaine dans l’affaire Social and Economic Rights Action Centre et un autre c. Nigéria et la jurisprudence de la Cour suprême d’Inde dans l’affaire KS Puttaswamy (Retd) et un Autre c. Union of India et autres, cet article explore la manière dont le droit à la vie privée peut être déduit des droits à la vie et à l’intégrité de la personne, du droit à la dignité ainsi que du droit à la liberté et à la sécurité de la personne. Cette contribution suggère que la déduction du droit à la vie privée d’autres droits garantis dans la Charte africaine est la voie la moins contraignante et la plus rapide qui soit. Elle atténue la nécessité de modifier la Charte africaine au regard de ses articles 66 ou 68. Enfin, cette contribution discute les raisons pour lesquelles il est nécessaire et important de déduire le droit à la vie privée d’autres droits garantis dans la Charte africaine et l’impact plus large que son caractère exécutoire peut avoir sur la réalisation significative du droit à la vie privée et des autres droits connexes en Afrique.
Keywords: privacy; right to life; right to dignity; right to liberty; security of the person; African Charter on Human and Peoples’ Rights; remedies